Patterns and Variation of Littoral Habitat Size Among Lakes. Issue 20 (11th October 2021) - Seekell, D.; Cael, B.; Norman, S.; Byström, P.
Abstract: The littoral zone varies in size among lakes from ∼3% to 100% of lake surface area. In this paper, we derive a simple theoretical scaling relationship that explains this variation, and test this theory using bathymetric data across the size spectra of freshwater lakes (surface area = 0.01–82, 103 km 2, maximum depth = 2–1, 741 m). Littoral area primarily reflects the ratio of the maximum depth of photosynthesis to maximum lake depth. However, lakes that are similar in these characteristics can have different relative littoral areas because of variation in basin shape. Hypsometric (area‐elevation) models that describe these patterns for individual lakes can be generalized among lakes to accurately predict the relative size of littoral habitat when there is incomplete bathymetric information. Collectively, our results provide simple rules for understanding patterns of littoral habitat size at the regional and global scales. Plain Language Summary: Some lakes are comprised completely by littoral habitat while other have almost none, but the factors responsible for this variation are poorly described. We developed simple relationships to explain variation in the size of littoral habitats among lakes. The factors determining littoral habitat size were light penetration, maximum depth, and mean depth. We make several predictions based on these rules including that alpine lakes should have large littoral zones compared to lakes in forested, agricultural, and urban regions, and that lakes should generally have larger littoral zones than reservoirs. We also derive simple equations that accurately predict the relative size of littoral zones in lakes where bathymetric data are incomplete. Collectively, our results and predictions elucidate the connection between lake characteristics and the relative size of habitats within lakes, which provides enough information to understand patterns of littoral habitat size at the regional to global scale. Key Points: Littoral area is smaller in deeper lakes and those with lower light penetration. The relationship is modified by basin shape Scaling relationships can predict the relative size of littoral area for lakes with incomplete bathymetric information The littoral zone comprises 78% of Earth's total lake area